The Creative Heritage of Valeria Fedorovna Orlova as the Basis of Domestic Forensic Handwriting Examination - Larisa V. Sidel’nikova; Inna R. Yagut’yan (Теория и практика судебной экспертизы)
The article is dedicated to the biography and scientific creativity of an eminent scientist, Doctor of Law, professor Valeria Fedorovna Orlova (18.01.1926–18.03.2021), who devoted her life to forensic handwriting examination. The author addresses V.F. Orlova’s main theoretical works and methodologies, and textbooks created under her supervision. The article introduces the main tasks and capacities of forensic handwriting examination in our country.